A method for producing environmentally friendly building materials using steel slag
Through the air quenching process and modification treatment technology, the problems of unstable performance and low strength of steel slag in building materials have been solved, and the production of environmentally friendly building materials with high strength and stable performance has been achieved.
Patent Information
- Application Number
- CN202410789119.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-19
AI Technical Summary
When steel slag is used as a building material, due to the presence of free calcium oxide and uneven active mineral distribution, the material performance is unstable, the strength is low, and there are problems of environmental pollution and safety hazards.
Liquid steel slag is made into uniform steel slag particles through the air quenching process, and magnetic separation and modification treatments are performed, including stirring in phosphoric acid, ultrasonic dispersion of silane coupling agent, application of electric field and addition of polyethylene short fibers to form a porous structure and linear Arranged short fibers improve the bonding between steel slag and filler.
It improves the combination of steel slag and other fillers, reduces the defects inside the building materials, significantly improves the structural strength and performance stability of the building materials, and at the same time realize the production of environmentally friendly building materials.
Smart Images

Figure CN118702430B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a method for producing environmentally friendly building materials by utilizing steel slag. Background Art
[0002] Steel slag is the molten slag discharged during the steelmaking process. It is a by-product of the steelmaking process. It mainly comes from the oxides formed by the oxidation of silicon, manganese, phosphorus and a small amount of iron in the metal charge. About 120-150kg of steel slag is produced for each ton of steel. These steel slags contain a large amount of usable components such as slag steel, calcium oxide, iron and magnesium oxide. If these steel slags are discarded at will, it will not only occupy land, waste resources, pollute the environment, but also pose serious safety hazards.
[0003] The recycling of steel slag mainly includes extracting valuable elements from steel slag, making building materials from steel slag, and using steel slag as filling materials and roadbed. Due to the presence of free calcium oxide in steel slag, when used as a building material, the free calcium oxide will react with water to cause volume expansion, resulting in defects inside the building material. In addition, the active minerals with hydraulic gel properties in the steel slag are unevenly distributed, and some steel slag cannot be well combined with other fillers, resulting in unstable performance and low strength of steel slag building materials. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for producing environmentally friendly building materials using steel slag.
[0005] The technical solution of the present invention is: a method for producing environmentally friendly building materials using steel slag, comprising the following steps:
[0006] S1. Preprocessing
[0007] The liquid slag discharged from the steel furnace is treated by an air quenching process, so that the liquid slag is sprayed with high-pressure air and cooled into slag particles, the slag particles are magnetically separated to remove the scrap steel particles in the slag particles, and then the slag particles are modified to obtain modified slag micro-beads;
[0008] S2. Mixing
[0009] The modified steel slag micro-beads, desulfurized gypsum powder and fly ash are uniformly mixed in a ratio of 50 to 70 parts by weight of the modified steel slag micro-beads, 20 to 30 parts by weight of the desulfurized gypsum powder and 10 to 20 parts by weight of the fly ash to obtain a mixture;
[0010] S3, pulping
[0011] Add 10-25% of water to the mixture and mix evenly to obtain the building material.
[0012] Description: The above method uses the air quenching process to make liquid steel slag into steel slag particles, so that the various components in the steel slag are evenly distributed, and the free calcium oxide in the steel slag will be digested under the action of high-pressure air. At the same time, the steel slag particles are modified to improve the bonding between the steel slag and other fillers, thereby improving the strength of the building material.
[0013] Furthermore, in step S1, the modification method is:
[0014] S1-1, placing steel slag particles in phosphoric acid and stirring for 2-3 hours, then taking out the steel slag particles and placing them in an ethanol solution, adding a silane coupling agent to the ethanol solution, and ultrasonically dispersing for 30-40 minutes to obtain a steel slag dispersion; the mass ratio of the steel slag particles, phosphoric acid, ethanol solution, and silane coupling agent is 1:3-5:2-4:0.2-0.4;
[0015] S1-2, applying an electric field to the steel slag dispersion and maintaining it for 20 to 30 minutes to obtain a mixed solution; the electric field strength is 1.5 to 3 kV / cm, the electric field frequency is 20 to 30 Hz, and polyethylene short fibers are added to the steel slag dispersion once every 8 to 10 minutes, and the single addition amount of polyethylene short fibers accounts for 5 to 10% of the total mass of the steel slag particles;
[0016] S1-3, filtering and drying the mixed solution to obtain modified steel slag microbeads.
[0017] Description: The above modification treatment forms a porous structure by treating the steel slag particles with phosphoric acid, and through the action of the electric field, the polyethylene staple fibers are arranged linearly and evenly loaded on the surface of the porous steel slag particles, thereby improving the binding between the steel slag particles and other fillers, reducing the defects inside the building materials, and improving the structural strength of the building materials.
[0018] Furthermore, the mass concentration of the ethanol solution is 50-75%.
[0019] Note: The ethanol solution of the above concentration has good solubility and can fully dissolve the silane coupling agent, so that the silane coupling agent can be hydrolyzed to release functional groups.
[0020] Furthermore, the silane coupling agent is a mixture of any one or more of 3-aminopropyltriethoxysilane, methyltrimethoxysilane and dodecyltrimethoxysilane in any ratio.
[0021] Description: The above silane coupling agent can stably connect the polyethylene staple fibers to the surface of the steel slag particles through the interaction between the active groups.
[0022] Furthermore, the length of the polyethylene staple fibers is 0.3 to 0.5 mm.
[0023] Note: Limiting the length of polyethylene staple fibers can ensure that the polyethylene staple fibers can be effectively loaded on the surface of steel slag particles.
[0024] Furthermore, in step S1-2, the frequency of the electric field is increased by 3 to 6 Hz each time polyethylene staple fibers are added.
[0025] Note: By gradually increasing the frequency of the electric field, the rate of change of the direction of the electric field can be gradually increased, ensuring that the surface of the steel slag particles can fully load the polyethylene short fibers.
[0026] Furthermore, the temperature of the liquid slag during wind quenching is 1450-1600° C., and the wind pressure during wind quenching is 0.5-1.0 MPa.
[0027] Note: The above-mentioned wind quenching parameters can ensure that the liquid slag can form uniform slag particles and ensure the cooling speed so that the free calcium oxide in the slag can be fully digested.
[0028] Furthermore, the particle size of the steel slag particles is ≤2 mm.
[0029] Note: Limiting the particle size of steel slag particles can ensure the uniformity of building materials and avoid the appearance of larger particles inside the building materials, which may lead to defects inside the building materials.
[0030] Furthermore, the fly ash is Class II fly ash.
[0031] Description: The composition of Class II fly ash is evenly distributed and has a large specific surface area. It can be effectively combined with modified steel slag microbeads to improve the strength of building materials.
[0032] The beneficial effects of the present invention are:
[0033] (1) The present invention uses an air quenching process to make liquid steel slag into steel slag particles, so that the various components in the steel slag are evenly distributed, and the free calcium oxide in the steel slag is digested under the action of high-pressure air. At the same time, the steel slag particles are modified to improve the bonding between the steel slag and other fillers, thereby improving the strength of the building material.
[0034] (2) The modification treatment of the present invention forms a porous structure by treating steel slag particles with phosphoric acid, and through the action of the electric field, the polyethylene short fibers are linearly arranged and evenly loaded on the surface of the porous steel slag particles, thereby improving the binding between the steel slag particles and other fillers, reducing the defects inside the building materials, and improving the structural strength of the building materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a bar graph of compressive strength of the test block of Experimental Example 1 of the present invention;
[0036] Figure 2is a bar graph of compressive strength of the test block of Experimental Example 2 of the present invention;
[0037] Figure 3 is a bar graph of compressive strength of test blocks of Experimental Example 3 of the present invention;
[0038] Figure 4 is a bar graph of compressive strength of the test block of Experimental Example 4 of the present invention;
[0039] Figure 5 is a bar graph of compressive strength of the test block of Experimental Example 5 of the present invention; DETAILED DESCRIPTION
[0040] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0041] Embodiment 1: A method for producing environmentally friendly building materials using steel slag, characterized in that it comprises the following steps:
[0042] S1. Preprocessing
[0043] The liquid slag discharged from the steel furnace is treated by an air quenching process, so that the liquid slag is sprayed with high-pressure air and cooled into slag particles, and the slag particles are magnetically separated to remove the scrap steel particles in the slag particles, and then the slag particles are modified to obtain modified slag micro-beads; wherein the temperature of the liquid slag during the air quenching is 1500°C, the air pressure during the air quenching is 0.7MPa; the particle size of the slag particles is ≤2mm
[0044] The modification method is:
[0045] S1-1, placing steel slag particles in phosphoric acid and stirring for 2.5 hours, then taking out the steel slag particles and placing them in an ethanol solution, adding a silane coupling agent to the ethanol solution, and ultrasonically dispersing for 35 minutes to obtain a steel slag dispersion; the mass ratio of the steel slag particles, phosphoric acid, ethanol solution, and silane coupling agent is 1:4:3:0.3; wherein the mass concentration of the ethanol solution is 60%, and the silane coupling agent is 3-aminopropyltriethoxysilane;
[0046] S1-2, applying an electric field to the steel slag dispersion and maintaining it for 25 minutes to obtain a mixed solution; the electric field strength is 2.2 kV / cm, the electric field frequency is 25 Hz, polyethylene short fibers are added to the steel slag dispersion once every 9 minutes, the single addition amount of polyethylene short fibers accounts for 8% of the total mass of the steel slag particles, and the electric field frequency increases by 5 Hz each time polyethylene short fibers are added; wherein the length of the polyethylene short fibers is 0.4 mm;
[0047] S1-3, filtering and drying the mixed solution to obtain modified steel slag microbeads;
[0048] S2. Mixing
[0049] The modified steel slag micro-beads, desulfurized gypsum powder and fly ash are uniformly mixed in a ratio of 60 parts by weight of the modified steel slag micro-beads, 25 parts by weight of the desulfurized gypsum powder and 15 parts by weight of the fly ash to obtain a mixture; wherein the fly ash is Class II fly ash;
[0050] S3, pulping
[0051] Add 18% water of the total mass of the mixture into the mixture, mix evenly and obtain the building material.
[0052] Example 2: This example is basically the same as Example 1, except that the mass ratio of steel slag particles, phosphoric acid, ethanol solution, and silane coupling agent is 1:3:2:0.2.
[0053] Example 3: This example is basically the same as Example 1, except that the mass ratio of steel slag particles, phosphoric acid, ethanol solution, and silane coupling agent is 1:5:4:0.4.
[0054] Example 4: This example is basically the same as Example 1, except that the electric field strength is 1.5 kV / cm.
[0055] Example 5: This example is basically the same as Example 1, except that the electric field strength is 3 kV / cm.
[0056] Example 6: This example is basically the same as Example 1, except that the electric field frequency is 20 Hz, and the electric field frequency increases by 3 Hz each time polyethylene staple fibers are added.
[0057] Example 7: This example is basically the same as Example 1, except that the electric field frequency is 30 Hz, and the electric field frequency increases by 6 Hz each time polyethylene staple fibers are added.
[0058] Example 8: This example is basically the same as Example 1, except that the single addition amount of polyethylene short fibers accounts for 5% of the total mass of the steel slag particles.
[0059] Example 9: This example is basically the same as Example 1, except that the single addition amount of polyethylene short fibers accounts for 10% of the total mass of the steel slag particles.
[0060] Example 10: This example is basically the same as Example 1, except that the modified steel slag microbeads, desulfurized gypsum powder and fly ash are uniformly mixed in a ratio of 50 parts by weight of modified steel slag microbeads, 20 parts by weight of desulfurized gypsum powder and 10 parts by weight of fly ash.
[0061] Example 11: This example is basically the same as Example 1, except that the modified steel slag microbeads, desulfurized gypsum powder and fly ash are uniformly mixed in a ratio of 70 parts by weight of modified steel slag microbeads, 30 parts by weight of desulfurized gypsum powder and 20 parts by weight of fly ash.
[0062] Comparative Example 1: Taking Example 1 as a reference, the mass ratio of steel slag particles, phosphoric acid, ethanol solution, and silane coupling agent is 1:2:1:0.1.
[0063] Comparative Example 2: Taking Example 1 as a reference, the mass ratio of steel slag particles, phosphoric acid, ethanol solution, and silane coupling agent is 1:6:5:0.5.
[0064] Comparative Example 3: Using Example 1 as a reference, no electric field was applied during the modification process.
[0065] Comparative Example 4: Taking Example 1 as a reference, the electric field frequency does not change.
[0066] Comparative Example 5: Taking Example 1 as a reference, the polyethylene staple fibers were added in one go.
[0067] Comparative Example 6: Taking Example 1 as a reference, unmodified steel slag microbeads were used instead of modified steel slag microbeads as a mixed material.
[0068] Comparative Example 7: Comparative Example 6 is used as a reference, and polyethylene short fibers are mixed with unmodified steel slag microbeads, desulfurized gypsum powder and fly ash to form a mixture.
[0069] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the building materials, the building materials of each embodiment were prepared into 70.7mm×70.7mm×70.7mm mortar test blocks. After curing for 28 days, the compressive strength test of the test blocks of each embodiment was carried out. The specific exploration is as follows:
[0070] 1. Explore the influence of modified raw material ratio on the performance of building materials
[0071] like Figure 1 As shown, by comparing Examples 1, 2, 3 and Comparative Examples 1 and 2, it can be seen that: as the proportions of phosphoric acid, ethanol solution and silane coupling agent gradually increase, the compressive strength of the test block also gradually increases, and the compressive strength of the test block of Example 1 reaches the highest; however, as the proportions of phosphoric acid, ethanol solution and silane coupling agent continue to increase, the compressive strength of the test block does not change significantly. This may be because the specific surface area of the steel slag particles is limited, and the amount of polyethylene short fibers that can be loaded cannot continue to increase. Therefore, from a cost perspective, the raw material ratio of the modified treatment selected in Example 1 is optimal.
[0072] 2. Explore the influence of electric field strength on the performance of building materials
[0073] like Figure 2 As shown, by comparing Examples 1, 4, and 5, it can be seen that the compressive strength of the test block in Example 1 reaches the highest, which may be because the electric field strength in Example 1 can effectively act on the polyethylene staple fibers, and the electric field does not affect the distribution of the slag particles, so that the polyethylene staple fibers can be evenly loaded on the surface of the slag particles, so the electric field strength selected in Example 1 is optimal;
[0074] By comparing Example 1 with Comparative Example 3, it can be seen that after removing the electric field, the compressive strength of the test block decreases significantly. This may be because the electric field can make the polyethylene short fibers linearly arranged and evenly loaded on the surface of the steel slag particles, thereby improving the binding properties of the steel slag particles with other fillers.
[0075] 3. Explore the influence of electric field frequency on the performance of building materials
[0076] like Figure 3 As shown, by comparing Examples 1, 6, and 7, it can be seen that the test block of Example 1 has the highest compressive strength. This may be because the electric field frequency will change the arrangement direction of the polyethylene short fibers, making the polyethylene short fibers more evenly distributed on the surface of the slag particles. However, too high an electric field frequency will cause the polyethylene short fibers to be unable to be effectively connected to the surface of the slag particles. Therefore, the electric field frequency selected in Example 1 is better.
[0077] By comparing Example 4 with Comparative Example 4, it can be seen that: the electric field frequency does not change, but the compressive strength of the test block decreases. This may be because the electric field frequency gradually increases, which accelerates the change speed of the arrangement direction of the polyethylene short fibers, allowing the surface of the steel slag particles to fully load the polyethylene short fibers.
[0078] 4. Explore the effect of polyethylene short fiber addition on the performance of building materials
[0079] like Figure 4 As shown, by comparing Examples 1, 8, and 9, it can be seen that: as the amount of polyethylene short fibers added increases, the compressive strength of the test block also gradually increases, and the compressive strength of the test block of Example 1 reaches the highest; however, as the strength of the polyethylene short fibers continues to increase, the compressive strength of the test block does not change significantly, which may be because the amount of polyethylene short fibers that can be loaded on the surface of the steel slag particles cannot continue to increase. Therefore, from a cost perspective, the polyethylene short fibers selected in Example 1 are the best;
[0080] By comparing Example 1 with Comparative Example 5, it can be seen that after the polyethylene staple fibers were added in a one-time manner, the compressive strength of the test block decreased. This may be because the one-time addition method caused the polyethylene staple fibers to agglomerate, resulting in the polyethylene staple fibers not being evenly loaded on the surface of the slag particles.
[0081] 5. Explore the influence of mixture composition on the performance of building materials
[0082] like Figure 5 As shown, by comparing Examples 1, 10, and 11, it can be seen that the compressive strength of the test block of Example 1 is the highest, which may be because the internal voids of the mixture of Example 1 are relatively small, and the bonding between the mixture particles is relatively strong, so the mixture composition selected in Example 1 is optimal;
[0083] From the comparison between Example 1 and Comparative Examples 6 and 7, it can be seen that after using the unmodified steel slag microbeads, the compressive strength of the test block is significantly reduced, and the polyethylene staple fibers are not loaded on the surface of the steel slag microbeads. The compressive strength of the test block can be improved by directly adding them into the mixture, but it is still lower than the steel slag microbead test block after the modification treatment in Example 1. This may be because directly adding the polyethylene staple fibers to the mixture will cause agglomeration, making it impossible for the polyethylene staple fibers to be evenly distributed in the mixture, and the modified steel slag microbeads have a stronger binding property with other particles.
Claims
1. A method for producing environmentally friendly building materials using steel slag, characterized in that: The following steps are involved: S1. Preprocessing The liquid slag discharged from the steel furnace is treated by an air quenching process, so that the liquid slag is sprayed with high-pressure air and cooled into slag particles, the slag particles are magnetically separated to remove the scrap steel particles in the slag particles, and then the slag particles are modified to obtain modified slag micro-beads; The modification method is: S1-1, placing steel slag particles in phosphoric acid and stirring for 2-3 hours, then taking out the steel slag particles and placing them in an ethanol solution, adding a silane coupling agent to the ethanol solution, and ultrasonically dispersing for 30-40 minutes to obtain a steel slag dispersion; the mass ratio of the steel slag particles, phosphoric acid, ethanol solution and silane coupling agent is 1:3-5:2-4:0.2-0.4; S1-2, applying an electric field to the steel slag dispersion and maintaining it for 20 to 30 minutes to obtain a mixed solution; the electric field strength is 1.5 to 3 kV / cm, the electric field frequency is 20 to 30 Hz, and polyethylene short fibers are added to the steel slag dispersion once every 8 to 10 minutes, and the single addition amount of polyethylene short fibers accounts for 5 to 10% of the total mass of the steel slag particles; S1-3, filtering and drying the mixed solution to obtain modified steel slag microbeads; S2. Mixing The modified steel slag micro-beads, desulfurized gypsum powder and fly ash are uniformly mixed in a ratio of 50 to 70 parts by weight of the modified steel slag micro-beads, 20 to 30 parts by weight of the desulfurized gypsum powder and 10 to 20 parts by weight of the fly ash to obtain a mixture; S3, pulping Add 10-25% of water to the mixture and mix evenly to obtain the building material.
2. The method for producing environmentally friendly building materials using steel slag according to claim 1, characterized in that: The mass concentration of the ethanol solution is 50-75%.
3. The method for producing environmentally friendly building materials using steel slag according to claim 1, characterized in that: The silane coupling agent is a mixture of any one or more of 3-aminopropyltriethoxysilane, methyltrimethoxysilane and dodecyltrimethoxysilane in any ratio.
4. The method for producing environmentally friendly building materials using steel slag according to claim 1, characterized in that: The length of the polyethylene short fibers is 0.3-0.5 mm.
5. The method for producing environmentally friendly building materials using steel slag according to claim 1, characterized in that: In step S1-2, the frequency of the electric field increases by 3 to 6 Hz each time polyethylene staple fibers are added.
6. The method for producing environmentally friendly building materials using steel slag according to claim 1, characterized in that: The temperature of the liquid slag during wind quenching is 1450-1600° C., and the wind pressure during wind quenching is 0.5-1.0 MPa.
7. The method for producing environmentally friendly building materials using steel slag according to claim 1, characterized in that: The particle size of the steel slag particles is ≤2 mm.
8. The method for producing environmentally friendly building materials using steel slag according to claim 1, characterized in that: The fly ash is Class II fly ash.
Citation Information
Patent Citations
Method for improving hydration activity of steel slag
CN103435278A
Building material prepared by synergistic carbonization of steel slag, desulfurized gypsum and fly ash and method
CN112430051A